Hanging and near hanging in children: injury patterns and a clinical approach to early management. Issue 2 (9th July 2018) - van Hasselt, Tim J; Hartshorn, Stuart
Abstract : Near hanging refers to survival following suspension by the neck. This is a devastating injury which can lead to mortality or serious long-term morbidity. Children and young people present to emergency departments following accidental or deliberate near hanging. This article describes the patterns of injury, the initial management and important prognostic factors.